If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4k = 4(7 + 6k) + 92 4k = (7 * 4 + 6k * 4) + 92 4k = (28 + 24k) + 92 Reorder the terms: 4k = 28 + 92 + 24k Combine like terms: 28 + 92 = 120 4k = 120 + 24k Solving 4k = 120 + 24k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-24k' to each side of the equation. 4k + -24k = 120 + 24k + -24k Combine like terms: 4k + -24k = -20k -20k = 120 + 24k + -24k Combine like terms: 24k + -24k = 0 -20k = 120 + 0 -20k = 120 Divide each side by '-20'. k = -6 Simplifying k = -6
| 3y-2=12-4y | | 1-2y=-x | | (+2)-(-6)= | | 1/2(a-16)=-9 | | 9m^2+100m+100=0 | | 3x+1=6x-14 | | -6x-8y=-48 | | (-6)-(0)= | | 14=8-x | | -7+5x=.2 | | 7(y-1.3)+2.4-5.3y= | | 20=0.8w | | -3=-3(2(1)-1) | | 4x+2+30=8+6x | | -2u+9=5 | | 8x+2y=14 | | 6k^2-43k-40=0 | | 20=0.8 | | 1.1x+1.2x-504=-10 | | 21x^2-59x+40=0 | | 2x(7X^2+3x)=56(x*x^2) | | 5(r-0.2)=13 | | 2(-6x+2)=-104 | | 6k^2-43k-20=0 | | 2n+6=3-.2n | | 5+1.5=3-2y | | -4x+3=93+6x | | 15=20n | | 19-3(4x+2y)= | | 8y(5y+2)=16 | | 9t^2-10t+1=0 | | -13x-5=8 |